DNA interference and beyond: structure and functions of prokaryotic Argonaute proteins - Lidiya Lisitskaya (Nature Portfolio, 2018)
In this review, Aravin and colleagues examine bacterial and archaeal Argonaute proteins, discuss their diverse architectures and their possible roles in host defense, proposing additional functions for Argonaute proteins in prokaryotic cells.